2014
DOI: 10.1128/aac.02830-14
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacokinetics of XOMA 3AB, a Novel Mixture of Three Monoclonal Antibodies against Botulinum Toxin A

Abstract: Botulinum neurotoxin A is a category A bioterrorism agent. Current antitoxin therapies are scarce and produce adverse reactions. XOMA 3AB consists of 3 IgG1 monoclonal antibodies (MAbs), each with a distinct human or humanized variable region, which bind to distinct epitopes on botulinum neurotoxin serotype A. This first-in-human study evaluated the safety and pharmacokinetics (PK) of escalating doses of XOMA 3AB administered intravenously (i.v.) to healthy adults. In this double-blind placebo-controlled dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 17 publications
2
71
0
Order By: Relevance
“…Due to the high degree of AA sequence identity between H C HA and H C A, it was expected that antibodies that target H C A are likely able to neutralize BoNT/HA and thus reduce this new threat to society. A recent study found that several antibodies could work in this regard, including RAZ1 and CR2, which are two of the three antibodies in the clinical-trial drug XOMA 3AB [40]. It was reported that RAZ1 (derived from 3D12) bound BoNT/HA tightly with a dissociation constant (K D ) of ~4.96 pM, almost as good as BoNT/A1 (~2 pM) [22].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high degree of AA sequence identity between H C HA and H C A, it was expected that antibodies that target H C A are likely able to neutralize BoNT/HA and thus reduce this new threat to society. A recent study found that several antibodies could work in this regard, including RAZ1 and CR2, which are two of the three antibodies in the clinical-trial drug XOMA 3AB [40]. It was reported that RAZ1 (derived from 3D12) bound BoNT/HA tightly with a dissociation constant (K D ) of ~4.96 pM, almost as good as BoNT/A1 (~2 pM) [22].…”
Section: Resultsmentioning
confidence: 99%
“…As a possible alternative to BAT, NTM-1631 [29], a combination of two human and one humanized BoNT/A mAbs (formerly XOMA 3AB), has been calculated to be at least ten times more potent than BAT for BoNT/HA using the mouse neutralization assay [12]. NTM-1631 has a serum half-life of >10 days and was well tolerated with no significant adverse events in a Phase 1 clinical trial [29]. Hence NTM-1631 could be developed as a treatment for botulism due to BoNT/HA.…”
Section: Discussionmentioning
confidence: 99%
“…There is no general scientific rule governing the rational selection of the appropriate number of antibodies in an oligoclonal mixture. There are examples where the combinations of multiple antibodies, typically three, showed a significant synergistic effect in vivo, such as in the case of antibodies against botulinum neurotoxin [44,45,46 ] and pertussis toxin [47]. Another example is the case of the three antibodies composing the Zmapp preparation which has been utilized on a compassionate basis, and recently in a randomized trial (that however failed to show a statistically significant effect [48]), to treat Ebola virus infections from the recent outbreak in West Africa [49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly for development of such therapeutics, the current guidance does specify that this requirement may be waived on ethical grounds if there are sufficient preclinical or clinical data indicating that the monotherapies would likely be ineffective or in cases where primary and/or acquired resistance are a significant concern. Indeed, the FDA on several occasions has allowed oligoclonal antibodies to be clinically tested as single products in Phase 1 and Phase 2 studies (such as for rabies [41], botulinum [44], the rhesus D antigen [107] and for the MM-151 and Sym004 anti-EGFR therapeutics in cancer). As no oligoclonal antibodies have, to date, filed for regulatory approval, we recommend that sponsors engage regulators early and often during development of these products and, as warranted, share their experiences with the community.…”
Section: Polyclonal and Bispecific Antibodies As Alternatives To Monomentioning
confidence: 99%